Are managers from Mars and academicians from venus? Toward an understanding of the relationship between academic quality and practical relevance - Baldridge, David; Floyd, Steven W.; Markóczy, Ĺıvia (Strategic Management Journal, 2004)
Abstract In this paper, we propose a positive relationship between the academic quality and practical relevance of management research. The basis for this is the idea that academicians and practitioners both value research that is interesting and justified—meaning research that challenges and extends existing beliefs and research that offers compelling evidence for its conclusions. We acknowledge that there are likely to be many cases where academicians and practitioners disagree on what is interesting and justified. We argue, however, that there are also likely to be cases where the judgments of the two groups converge. Results from a stratified, random sample of 120 publications are consistent with this argument—showing a positive correlation between an objective measure of an article's academic quality and expert panel ratings of its practical relevance. The analysis also shows positive associations between panel members' global assessment of relevance and ratings of an article's interestingness and justification. These results lend support to the hypothesized overlap, but leave room for considerable difference in the way practitioners and academicians evaluate management research. Copyright © 2004 John Wiley & Sons, Ltd.